ASYMPTOTIC BEHAVIOR FOR A PROBLEM OF TRANSMISSION WITH NONLINEAR DAMPING LOCALLY DISTRIBUTED AND MEMORY IN THE BORDER - Perez Salvatierra, Alfonso (2011)
We will study the asymptotic Behavior for a problem of transmission nonlinear with damping locally distributed and with memory at the chosen to boundary for the system following,